Clinicopathological Characteristics and Survival Outcome among Patients with Renal Cell Carcinoma: A Northern Malaysian Experience - Seo, Yiie Huern (South Asian Journal of Cancer, 2025)
Renal cell carcinoma (RCC) is the 12th highest cause of cancer mortality in Malaysia with 532 deaths recorded in 2020. This study aims to determine the prognostic significance of the clinicopathological factors among RCC patients at a Malaysian hospital.Medical records of 104 patients with confirmed primary RCC who underwent nephrectomy from 2015 to 2020 at our center were retrospectively reviewed. The relationship between clinical and histopathological data and survival was studied using univariate and multivariate Cox regression analyses to determine prognostic significance. Kaplan–Meier and log-rank tests were employed for survival analysis.The 5-year cancer-specific survival was 71.2% with a median follow-up of 14 months (interquartile range 5–38 months). Symptoms of loin pain (p = 0.004, hazard ratio [HR] 2.9) or anemia (p = 0.001, HR: 3.6), lower body mass index (p = 0.001, HR 0.88), smoking (p = 0.002, HR 3.3), larger tumors (p < 0.001, HR 1.2), nodal involvement (p < 0.001, HR 7.6), higher International Society of Urological Pathology (ISUP) grade (p < 0.001, HR 2.7), and sarcomatoid features (p < 0.001, HR 16.6) have worse prognosis. Multivariate analysis, adjusted for TNM stage, found smoking (p = 0.002, HR 3.3), larger tumor size (p = 0.048, HR 1.1), nodal involvement (p = 0.009, HR 2.8), higher ISUP grade (p = 0.010, HR 2.0), and sarcomatoid histology (p = 0.001, HR 5.8) to be independent prognostic parameters for overall survival.Detection and treatment of RCC before symptomatic onset or metastases confer a better prognosis. A history of smoking negatively affects survival. Presence of nodal involvement, venous infiltration, or sarcomatoid component in histopathological study was significantly associated with increased mortality.
Keywords: clinicopathological; Malaysia; prognosis; renal cell carcinoma; survival